Unilateral laryngeal immobility post-arbovirose: Case report (Research, Society and Development, 2020)
Laryngeal immobility is a disease usually associated with involvement of the recurrent laryngeal nerve, which can have a traumatic, tumor, infectious cause, among others. In its clinical presentation we have dysphonia with its social and economic impacts, leading to its importance of adequate diagnosis and treatment. The objective of this case report is to describe the clinical picture of a young female patient with dysphonia due to left vocal fold paresis, possibly resulting from infection by arbovirus (Dengue and \ or Chikungunya) and that significant clinical improvement was obtained after phonotherapy treatment. This atypical complication of arbovirus disease, never described, is based on the description of neuropathies and paralysis in other nerves already published. As a conclusion, it is suggested that serology research for arboviruses enter the arsenal to assess the possible etiologies of laryngeal immobility, when there is an epidemiology that justifies, as well as, the importance of speech therapy in the treatment of these patients with laryngeal immobility is reiterated.